Skeletal muscle heat shock protein 70: diverse functions and therapeutic potential for wasting disorders - Senf, Sarah M. (Frontiers in Physiology, 2013)
The stress-inducible 70-kDa heat shock protein (HSP70) is a highly conserved protein with diverse intracellular and extracellular functions. In skeletal muscle, HSP70 is rapidly induced in response to both non-damaging and damaging stress stimuli including exercise and acute muscle injuries. This upregulation of HSP70 contributes to the maintenance of muscle fiber integrity and facilitates muscle regeneration and recovery. Conversely, HSP70 expression is decreased during muscle inactivity and aging, and evidence supports the loss of HSP70 as a key mechanism which may drive muscle atrophy, contractile dysfunction and reduced regenerative capacity associated with these conditions. To date, the therapeutic benefit of HSP70 upregulation in skeletal muscle has been established in rodent models of muscle injury, muscle atrophy, modified muscle use, aging, and muscular dystrophy, which highlights HSP70 as a key therapeutic target for the treatment of various conditions which negatively affect skeletal muscle mass and function. This article will review these important findings and provide perspective on the unanswered questions related to HSP70 and skeletal muscle plasticity which require further investigation.